2013
DOI: 10.1177/1538574413491636
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Percutaneous Transluminal Angioplasty of the Profunda Femoris Artery for Limb Ischemia

Abstract: These contemporary data suggest isolated ePFRs and ePFR + eFPRs are associated with good and comparable early limb salvage rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Concomitant interventions on the aortoiliac segment or the SFA were undertaken in 60% of patients. 13–15,18,2628,31,33,35,39,40 Angioplasty alone was undertaken in 68.8% of treated patients. Angioplasty followed by selective or routine (three studies stenting was performed in 22.3% of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant interventions on the aortoiliac segment or the SFA were undertaken in 60% of patients. 13–15,18,2628,31,33,35,39,40 Angioplasty alone was undertaken in 68.8% of treated patients. Angioplasty followed by selective or routine (three studies stenting was performed in 22.3% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…1240 Twenty of these reports were included after final review by the authors. 1216,18,19,21,22,2528,31,33,3537,39,40 After reviewing the full paper, data regarding patient numbers and demographics, indications, pre- and post-intervention ankle-brachial index (ABI), site of intervention, and patency of SFA, technical success, type of endovascular approach, complications, patency and mortality rates were extracted and analyzed (Table 1).
Figure 1.Flow diagram for inclusion and exclusion of relevant clinical reports.
…”
Section: Methodsmentioning
confidence: 99%
“…However, it has been confirmed that this collateral circulation plays an important role in chronic occlusions, when there has been sufficient time to allow their development. In the same way, Davies et al 12 compared the outcomes of endovascular PFA revascularization (ePFR) with ePFR and concurrent endovascular femoropopliteal revascularization. They reported 12-month amputation-free survival and reintervention rates of 78% and 72% following isolated ePFR, and 96% and 81% following ePFR and concurrent endovascular femoropopliteal revascularization, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…19 The 12-month amputation-free survival and reintervention-free survival rates were 78% and 72%, respectively. 24 There are a number of limitations to our analysis. First, it is a self-reported retrospective study.…”
Section: Discussionmentioning
confidence: 99%